PENGARUH STRES TERHADAP KINERJA ANGGOTA POLRI DI POLRES PULAU BURU - Dewi Rizky. G. Hehanussa; Laura Huwae; Vina Z. Latuconsina (Fakultas Kedokteran Universitas Pattimura, 2020)
Everyone has experienced feelings of stress or stress. Stress can arise from a variety of sources, including demands. Work demands can be a potential source of stress. Potential sources of stress trigger the onset of stress related to performance and psychological events of the employee. This research aims to determine whether there is an effect of stress on the performance of members of the police at the Buru island. This research is a correlative analytic study with cross sectional approach. The research subject is 85 people who were selected using simple random sampling. The analysis used in this study was the chi square test, with the variables studied were stress and the performance of the police. The results of the research showed that the stress level of the police was most in the category of frequent stress by 54.1% and the category of stress rarely experienced as much as 45.9%, while the performance of police with the largest percentage was in the quite good category of 49.4%, followed good performance by 28.2%, and poor performance by 22.4%. The results of this research indicate that there is an influence between stress on the performance of members of the police in the Buru island (p = 0.014).